Mapping bee forage trees - Moskalenko, A.; Domina, I. (Land Management, Cadastre and Land Monitoring, 2019)
The possibility of using the data of remote sensing of the Earth for identification of the nectar and dustpans of perennial plants as a forage base of beekeeping is discussed. The key components for achieving the research objectives are identified and structured in the functional model. The thematic processing of the data of remote sensing of the Earth was carried out and the optimum period of identification of honey-bearing trees of the forage base of beekeeping was determined.Keywords: Earth remote sensing data, beekeeping feed base, classification of images